Nūr Muhammad Urang Banjar as Sufistic Psychotherapy - Muhammad Rusydi; Muhammad Syafi'i; Muhammad Rafi’ (Universitas Islam Negeri Mataram, 2022)
This field research with descriptive qualitative method aims to reveal the relationship between philosophical Sufism and psychology, namely the teachings of Nūr Muhammad in the Banjar Society with sufistic psychotherapy. It is found that the teachings of Nūr Muhammad who lived in the Banjar community are present through the books of sufism, recitation, and the tradition of qasidah or maulid poetry. Through the perspective of sufistic psychotherapy, Nūr Muhammad played the role of haqīqah al-haqāiq for consciousness therapy, Nūr Muhammad as jam’ al-jama for the development of love and crace therapy, Nūr Muhammad in shalawat as sound therapy and peace of mind.